PERANCANGAN PADA WEBSITE HERBAL BERBASIS SEARCH ENGINE OPTIMIZATION (SEO) UNTUK MENINGKATKAN VISIBILITAS PENCARIAN - Triga Agus Sugiarto; Maryama Kurnia Amri; Joko Prasetiana (LPPM Unbaja, 2026)
In this regard, search engines play a crucial role in helping users access information quickly and efficiently. If a website optimally utilizes Search Engine Optimization (SEO) and is well-indexed in Google, it has the potential to increase visibility and attract more visitors. Smart System Laboratory created a website to promote its herbal products. However, high competition from similar websites and a lack of marketing strategies are major obstacles to achieving high search engine rankings. SEO has become an effective strategy for improving website performance through optimizing keywords, page structure, and content quality, enabling it to appear in relevant search results. Several previous studies have shown that SEO implementation has a positive impact on website rankings, indexing quality, and visibility in Google search results pages (SERPs). On-page optimization, such as keyword usage, meta tags, and website content structure, as well as off-page optimization, such as backlinks and domain credibility, contribute to improving a website's position in search engines. Based on the aforementioned issues, this study uses SEO strategies to improve the performance of Smart System Laboratory's herbal product website. The goal of this study is to improve the herbal product website's ranking in Google search results and increase the number of website visitors. The results are expected to provide practical recommendations for implementing appropriate SEO strategies so that herbal product websites can compete competitively and achieve higher rankings in Google search results.